A novel flow arrangement of staggered flow in double-layered microchannel heat sinks for microelectronic cooling. (December 2016) - Zhai, Yuling; Xia, Guodong; Li, Zhouhang; Wang, Hua
Abstract: A novel flow arrangement of staggered flow (the fluid staggers flow along each layer) is presented to remove higher heat flux and obtain more uniform bottom temperature in double-layered microchannel heat sinks. Compared to the counter flow, the heat transfer performance of two types of staggered flow is studied numerically. The distribution of the total temperature, average bottom temperature, maximum temperature difference and thermal resistance is presented for different flow arrangements under similar pumping power. The results show that the flow arrangement with staggered flow 2 (the fluid flows along the x direction at the second layer, while fluid staggers along the y direction at the first layer) provides the lowest maximum and most uniform temperature under similar working condition. Moreover, the thermal resistance of staggered flow 2 is much lower than that of counter flow and staggered flow 1 under the similar pumping power, which indicates that it has better cooling capacity for microelectronic cooling. Highlights: Staggered flow (the fluid staggers flow along each layer) in double-layered microchannel heat sinks is presented. The distribution of temperature fields and thermal resistance is investigated numerically. Staggered flow 2 shows the most uniform temperature distribution and lowest thermal resistance under similar pumping power.